Phytochemical and insecticidal activity of Orthosiphon stamineus leaves extracts against rice weevils (Sitophilus oryzae L.) / Nurshahira Ismail - Ismail, Nurshahira (2015)
The percentage yield of crude extracts calculated found that methanol showed the highest percentage followed with chloroform and petroleum ether with 4.10, 3.23, 0.66 % respectively. The three different types of extract leaves of 0. stamineus were screened for secondary metabolite constituents and insecticidal activity against rice weevils (s. oryzae). The leaves sample were extracted with different solvent, petroleum ether, chloroform and methanol. Phytochemical screening of the extracts revealed the presence of alkaloids, flavonoids, saponins, steroids, tannins, and terpenoids in the plants investigated. However, steroids and alkaloids absence in the petroleum ether extract and while in chloroform absence of terpenoids and saponins and methanolic extract absence of terpenoids. The extracts of 0. stamineus of different concentrations were also investigated for their insecticidal activity against S. oryzae. The concentration were used at 250 ppm, 500 ppm, 1000 ppm, 2000 ppm and 4000 ppm. Average mortality indicated that the extracts caused significant mortality on the target insects. The bioassay has indicated that the toxic effect of the extracts was proportional to the concentration and higher concentration has stronger effect. From the study, petroleum ether extract of 0. stamineus could cause the highest significant mortality compared to chloroform and methanolic extract. The probit analysis was done to determine lethal concentration on controlling 50% of mortality rate of rice weevils. The LD50 for the petroleum extract is 1,697, for chloroform extract is 24,863 and for the methanol extract is 29,084 ppm. The TLC analysis is used as confirmation of secondary metabolite found in the extracts of 0. stamineus. Thus, 0. stamineus plant extract could be used as bio-pesticide against rice weevils so as to protect stored grains.